Disintegration Tendencies in the Contemporary International Order. Separatism, Secession, Revolution - Pobóg-Lenartowicz, Maria; Rojek, Karolina (The Copernicus Journal of Political Studies, 2018)
The processes of separation and unification of states and state systems are permanent elements in international relations. Alongside national development, the ethnic factor became another cause for both integration, as well as fragmentation of states. Nowadays, in Europe and in the world both tendencies appear. We are dealing with aspirations to unify, to focus on shared values, and parallel – to emphasise separateness and separate identity in external relations and inside multinational states. This article concentrates on the disintegration tendencies in the contemporary international order: separatisms, secessions and revolutions. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14760